2023
DOI: 10.1186/s40580-023-00369-3
|View full text |Cite
|
Sign up to set email alerts
|

Applications of remote epitaxy and van der Waals epitaxy

Abstract: Epitaxy technology produces high-quality material building blocks that underpin various fields of applications. However, fundamental limitations exist for conventional epitaxy, such as the lattice matching constraints that have greatly narrowed down the choices of available epitaxial material combinations. Recent emerging epitaxy techniques such as remote and van der Waals epitaxy have shown exciting perspectives to overcome these limitations and provide freestanding nanomembranes for massive novel application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…Another widely used transfer method is mechanically lifting off epilayers grown using an intermediate layer that facilitates mechanical exfoliation, such as 2D materials with atomic-layered structures. For example, GaN layers grown on graphene layers using van der Waals epitaxy could be easily released from the growing substrate . In addition, it has been found that high-quality thin films could be epitaxially grown even in the presence of 2D materials, because epitaxial orientation of the substrate could penetrate the 2D materials (known as remote epitaxy) .…”
Section: Materials For Flexible and Stretchable Ledsmentioning
confidence: 99%
“…Another widely used transfer method is mechanically lifting off epilayers grown using an intermediate layer that facilitates mechanical exfoliation, such as 2D materials with atomic-layered structures. For example, GaN layers grown on graphene layers using van der Waals epitaxy could be easily released from the growing substrate . In addition, it has been found that high-quality thin films could be epitaxially grown even in the presence of 2D materials, because epitaxial orientation of the substrate could penetrate the 2D materials (known as remote epitaxy) .…”
Section: Materials For Flexible and Stretchable Ledsmentioning
confidence: 99%
“…4b). 348 Besides, 2D materials that have a minuscule thickness limit their interaction length with electromagnetic waves, 50 and recent advances on remote epitaxy [371][372][373] and van der Waals epitaxy [374][375][376] also permit various three-dimensional (3D) freestanding nanomembranes (Fig. 4c), 50,375,[377][378][379][380] as well as other 3D layer exfoliation techniques by epitaxial chemical lift-off, mechanical exfoliation or laser lift-off.…”
Section: Perspectivesmentioning
confidence: 99%
“…Furthermore, despite the large lattice mismatch, the high-quality epilayer can be achievable where the remote epitaxy is implemented. The high-quality epilayers prepared by remote epitaxy provide various opportunities of advanced device manufacturing and realization of heterostructures composed of incommensurate materials due to their quality and releasable structures [ 93 ].…”
Section: General Categories Of Epitaxymentioning
confidence: 99%